(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The capital banking foundation stone upon which the bank in the practice of business activities, the more capital a good financial adequacy of the increased bank’s ability to grant credit and expand the various activities and provide a safety element for depositors and other sources of funding to achieve profits and increase the trading volume of the shares, causing the rise the rate of return for the shares of banks and have the Central Bank as head of the banking system by issuing instructions capital increase banking, according to the requirements of economic development and increase gross domestic product by supporting investment projects that are financed through banks, the research aims to show the extent of the banks commitment to the instructions of the Iraqi Central Bank to raise capital banking and its impact on the rate of earnings per share and the premise that the bank capital increase and invest properly contributes to the high rate of return for the shares of these banks and the application of financial standards and statistical techniques to prove the capital relationship with a rate of return on the share price and the most important findings of the researcher that the detention of bank profits in order to increase capital property had a negative impact on earnings per share for banks rate.